Coming together for something good: recommendations from a scoping review for dissemination and implementation science to improve indigenous substance use disorder treatment - Hirchak, Katherine A.; Oluwoye, Oladunni; Nadeau, Melanie; Richardson, Meenakshi; Bajet, Kelsey; Brigman, Mariah; Herron, Jalene L.; Hernandez-Vallant, Alexandra; Vasquez, Angel; Pham, Cuong; Oliver, Karen Anderson; Baukol, Paulette; et al. (Frontiers in Public Health, 2023)
Introduction: Dissemination and Implementation (D&I) science is growing among Indigenous communities. Indigenous communities are adapting and implementing evidence-based treatments for substance use disorders (SUD) to fit the needs of their communities. D&I science offers frameworks, models, and theories to increase implementation success, but research is needed to center Indigenous knowledge, enhancing D&I so that it is more applicable within Indigenous contexts. In this scoping review, we examined the current state of D&I science for SUD interventions among Indigenous communities and identified best-practice SUD implementation approaches. Methods: PubMed and PsycINFO databases were queried for articles written in English, published in the United States, Canada, Australia, and New Zealand. We included key search terms for Indigenous populations and 35 content keywords. We categorized the data using the adapted and extended Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM) framework that emphasizes equity and sustainability. RE-AIM has also been used as a primary model to consistently identify implementation outcomes. Results: Twenty articles were identified from the original unduplicated count of over 24,000. Over half the articles discussed processes related to Reach, Adoption, and Implementation. Effectiveness was discussed by 45% of the studies (n=9), with 25% of the articles discussing Maintenance/sustainability (n=5). Findings also highlighted the importance of the application of each RE-AIM domain for meaningful, well-defined community-engaged approaches. Conclusion: Finding indicated a need to prioritize Indigenous methods to culturally center, realign and adapt Western treatments and frameworks to increase health equity and improve SUD treatment outcomes. Utility in the use of the modified RE-AIM and the continued modification for Indigenous communities was also noted.